From Scarcity to Impulsive Buying Behavior: The Importance of Perceived Sellout Risk in the Context of TikTok Live Shopping - Florencia Jierussel; Jesslyn Aurelya Chandra; Charlyn Elizabeth Jocelyn Hamdali; Marsya Lilyan Wijaya; Vangeline Mevica Thevianny; Elia Ardyan (Accounting Profession Journal (APAJI), 2026)
In live streaming e-commerce, independent sellers who conduct live broadcasts commonly employ scarcity messages. The impact of these messages prompts consumers to process information with relatively low cognitive effort, leading them to implicitly conclude that the product is rare, difficult to obtain, and therefore perceived as valuable and appealing. This perception generates an urgency that drives consumers to make purchases before the offer ends, thus accelerating their decision-making process. This study examines how the fear of missing out on limited-time offers and limited quantities influences purchasing decisions during live streaming, particularly how concerns about items selling out lead to impulsive online buying. A quantitative research approach was employed, utilizing a structured questionnaire survey distributed to TikTok Shop users as the primary data collection tool. Data were collected from 210 respondents who had previously made purchases via TikTok live streaming. Data analysis was conducted using WarpPLS 8.0 software to assess validity and reliability and to test the hypotheses. The results of this study indicate that limited time scarcity and perceived sellout risk are able to increase significantly. Limited-time scarcity has a positive and significant effect on online impulsive buying, while limited-quantity scarcity has a positive and insignificant effect on online impulsive buying. Other results indicate that perceived sellout risk is able to increase online impulsive buying significantly.